Screening for Intimate Partner Violence in a Pediatric ED: A Quality Improvement Initiative. Issue 12 (7th December 2021) - Mancheno, Christina; Aumaier, Brenna; Murray, Ashlee
Abstract : Objective: Intimate partner violence (IPV) is a serious public health concern and impacts the entire family unit, particularly children. We implemented an IPV screening and referral program in an urban pediatric emergency department (ED) and aimed to screen 30% of patient families for IPV by January 1, 2017. Methods: We used a quality improvement initiative using a nonverbal screening card to screen families when the caregiver was the sole adult present and spoke English and/or Spanish, and the patient was medically stable. Interventions included education, culture of screening initiatives, feedback, and process changes to emergency medical record (EMR) documentation. The primary outcome measure was percentage of caregivers screened in the ED over time. Our balancing measure was ED length of stay. Results: After process improvement implementations that include requiring IPV screen documentation in the EMR, using Research Electronic Data Capture for referrals, and standardizing and simplifying the screening process, caregiver screening rates increased to 30% and have remained consistently at or above that rate during the 15-month postevaluation phase. This intervention did not impact length of stay in the ED. Conclusions: An innovative multiphase quality improvement approach to screen for IPV using a nonverbal screening card and technology within the EMR was successfully implemented in our pediatric ED. Both IPV screening and documentation rates demonstrated greatest improvement and sustainability after process improvements over other initiatives.